2018
DOI: 10.21037/jtd.2018.04.118
|View full text |Cite
|
Sign up to set email alerts
|

The history of lung transplantation in Hong Kong

Abstract: Clinical lung transplant was first performed in Hong Kong in 1995. In the early years, the volume of activity was very low. There has been a clear trend of increasing volume in the past few years. The recipient pathology is very different from the International Society for Heart and Lung Transplantation (ISHLT) database, with complete absence of cystic fibrosis and alpha-1-antitrypsin deficiency, and a predominance of diseases of the pulmonary circulation. Lymphangioleiomyomatosis (LAM) has a much higher repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Missing data in the present cohort was not excessive at 4.16% and were tackled by multiple imputations. However, our study was limited due to the relatively small sample size due to the relatively small service volume of lung transplantation in our city 21 . In addition, being a city with a predominant Asian population, might limit the generalizability of our data to the other part of the world.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Missing data in the present cohort was not excessive at 4.16% and were tackled by multiple imputations. However, our study was limited due to the relatively small sample size due to the relatively small service volume of lung transplantation in our city 21 . In addition, being a city with a predominant Asian population, might limit the generalizability of our data to the other part of the world.…”
Section: Discussionmentioning
confidence: 97%
“…However, our study was limited due to the relatively small sample size due to the relatively small service volume of lung transplantation in our city. 21 In addition, being a city with a predominant Asian population, might limit the generalizability of our data to the other part of the world. An additional multicenter study involving different countries may be needed to confirm our findings.…”
Section: Discussionmentioning
confidence: 98%
“…We showed that the APACHE IV score had satisfactory predictive performance for hospital mortality after ECMO, while the ICU LOS of our cohort was consistently longer than predicted. There may be characteristics in the Hong Kong healthcare infrastructure that lead to systematic over-or under-performance of actual outcomes, such as the relative lack of destination therapy including organ transplantation after end-stage organ failure (25), the finding that no patient over 10 years was bridged from V-V ECMO to lung transplantation affirms this observation (26). The low costs of hospital stay in publicly funded healthcare institutions may skew length of stay data.…”
Section: Discussionmentioning
confidence: 99%
“…Among indication categories, LAM, bronchiolitis obliterans (BO), and interstitial lung diseases have shown the best survival, while the worse came from pulmonary circulation diseases. The age range of potential candidates for evaluation has been expanded to 65 in recent years (26).…”
Section: Investigation On Practice Of Lung Transplantation In Asiamentioning
confidence: 99%